A Voxel‐based lesion study on facial emotion recognition after circumscribed prefrontal cortex damage. Issue 3 (17th February 2021) - Ouerchefani, Riadh; Ouerchefani, Naoufel; Kammoun, Brahim; Ben Rejeb, Mohamed Riadh; Le Gall, Didier
Abstract : Previous studies have shown inconsistent findings regarding the contribution of the different prefrontal regions in emotion recognition. Moreover, the hemispheric lateralization hypothesis posits that the right hemisphere is dominant for processing all emotions regardless of affective valence, whereas the valence specificity hypothesis posits that the left hemisphere is specialized for processing positive emotions while the right hemisphere is specialized for negative emotions. However, recent findings suggest that the evidence for such lateralization has been less consistent. In this study, we investigated emotion recognition of fear, surprise, happiness, sadness, disgust, and anger in 30 patients with focal prefrontal cortex lesions and 30 control subjects. We also examined the impact of lesion laterality on recognition of the six basic emotions. The results showed that compared to control subjects, the frontal subgroups were impaired in recognition of three negative basic emotions of fear, sadness, and anger – regardless of the lesion laterality. Therefore, our findings did not establish that each hemisphere is specialized for processing specific emotions. Moreover, the voxel‐based lesion symptom mapping analysis showed that recognition of fear, sadness, and anger draws on a partially common bilaterally distributed prefrontal network.